Analysis of Factors Affecting Farmer Exchange Rate of Food Crop Subsector in Indonesia - Tasya Sellinawaty (Universitas Negeri Semarang, 2024)
This study aims to analyze the factors that can affect the exchange rate of food crop farmers in Indonesia. The data used is sourced from the Central Bureau of Statistics and the Directorate General of Food Crops of Indonesia. Using panel data of 33 provinces in Indonesia during 2016-2021, this study applies the cointegration test to determine the long run of the research variables, and uses fully modified ordinary least square regression to determine the estimation amount of each independent variable in the long run with the Eviews 12 tool. The regression results explain that simultaneously, the research variables used together influence the exchange rate of food crop farmers in the long run. Partially, the variables of rice land area, secondary crop land area, and rice production have a significant positive effect on the exchange rate of food crop farmers in the long run. While the variables of inflation and secondary crop production have a significant negative effect on the exchange rate of food crop farmers in the long term.